Factors affecting the self-management practices of people with type 2 diabetes in Almadinah, Saudi Arabia - Aljohani, Khalid A. (Curtin University, 2011)
In the Middle Eastern Gulf Cooperation Countries, the prevalence of type 2 diabetes mellitus (T2DM) is increasing steadily. It has recently been estimated that up to 23% of the Saudi Arabian population meet the diagnostic criteria. Due to the potential for serious micro and macro-vascular complications such as peripheral vascular disease and nephropathy, T2DM places a significant burden on the individuals concerned and their families. In addition, T2DM is having catastrophic consequences for the health-care systems of many countries that are unable to cope with the increased demand for services. Furthermore, the prevalence is expected to increase and the burden of the disease is expected to worsen. As a consequence the Saudi government is implementing a number of strategies to address the issue, such as the National Plan to Combat Diabetes. The major problem is that T2DM is largely a lifestyle disease caused by an affluent diet and inactivity, and the goal of effective glycaemic control is impossible without competent patient self-management.This study identified factors affecting self-management practices among people who have T2DM in Almadinah, Saudi Arabia. The study had three phases. The first phase involved the development of a valid questionnaire instrument to measure diabetes self-management practices in Arabic speaking populations. The Summary of Diabetes Self-care Activities (SDSCA) instrument was translated into Arabic and validated according to the World Health Organisation’s Steps of Translation and Adaptation of Instruments. Two samples of T2DM participants were purposively recruited in this phase. The first sample consists of 33 while the second was 210 participants. Translation indicators showed satisfactory outcomes for each stage of the process.The Arabic Summary of Diabetes Self-care Activities (ASDSCA) instrument proved to have very acceptable psychometric properties: splithalf reliability (.90); test-retest (.912, p = <.001); and Cronbach’s alpha (.76). The internal consistency of the instrument’s sub-scales was good for diet (.89), exercise (.83), blood glucose testing (.92), and foot care (.77). Factor analysis revealed the presence of four components explaining 34.4%, 16%, 15.4%, and 11.2% of the variance of daily self-management practices for these items respectively (accumulated total of 77.1%). Based on these outcomes, the A-SDSCA was utilised in the second phase of the study.The second phase of the study measured diabetes self-management practices and identified socio-demographic factors affecting these practices. The sample of 210 T2DM participants purposively recruited from three primary health-care centres completed the A-SDCA (N=1,477). HbA1c scores indicated that only 30 (14.7%) participants had controlled blood glucose level (_ 7%). Bivariate analyses showed that blood glucose testing (85% _ four days/week) and exercise (47% _ two days/week) were the least practiced self-management activities. In contrast, selfmanagement levels were greatest for medication (75% 7days/week), diet (71% _ three days/week), and foot-care (56% _ three days/week). A regression model showed that high blood glucose level (-.122, p = .050) and smoking (-.192, p = .004) were negatively associated with self-management practices. On the other hand, being female (.321, p = .000) and having a good income (.129, p = .050) were positive factors. Overall, these factors accounted for 25% of the variability in everyday selfcare practices (R² = .251).The third phase further explored factors affecting self-management practices, not identified by the questionnaire alone. Using semi-structured interviews, qualitative data were collected from 24 T2DM participants and 12 health-care providers. Raw data were analysed by means of quantitative thematic analyses using the Chronic Care Model (CCM) as the conceptual framework. The result identified 30 sub-themes under the six CCM domains (themes). In total, 365 related statements were extracted. Major inputs were derived from health-care providers’ interviews (132 statements) followed by female (118 statements) and then male (115 statements) T2DM participants. Community domain was the most frequently identified theme (100 statements; 27%) while health system was the least frequently identified (38 statements; 10%). Factors relating to delivery system; decision making; clinical information system; and self-management represented 20%, 11%, 14% and 17% of the total identified statements, respectively.In conclusion, the fact that only 15% of participants had controlled glycaemic level despite a high level of dependence on medications is very good evidence that medication alone, is not the complete answer to the effective management of T2DM in the study context. The fact that the study participants demonstrated low levels of compliance with most other self-management practices indicates that they were facing difficulties and obstacles to practice optimal self-management activities. Furthermore, these findings reflect serious limitations in the way T2DM self-management is promoted and enhanced in the various study locations. The ASDSCA could be utilized by health-care researchers to measure self-management practices among T2DM people. Furthermore, the instrument might be used to measure improvements in self-management practices before and after self-management programs application.